2015
DOI: 10.1159/000439079
|View full text |Cite|
|
Sign up to set email alerts
|

Real-Life Clinical Practice with Sorafenib in Advanced Hepatocellular Carcinoma: A Single-Center Experience Second Analysis

Abstract: Objectives: Sorafenib has become a standard therapy for advanced hepatocellular carcinoma following the demonstration of significant increase in progression-free survival as well as overall survival (OS) in the 2-phase III trials. We examined efficacy and adverse events (AEs) in patients treated with sorafenib over a 6-year period since approval in Japan. Methods: Two hundred and forty-one patients treated with sorafenib at the Kinki University Hospital were retrospectively analyzed clinically for the factors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
10
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 41 publications
0
10
0
Order By: Relevance
“…In the present muscle‐atrophy group, muscle wasting after starting sorafenib might have more frequently caused fatigue, asthenia, and physical disability compared to the non‐atrophy group, and resultant physical changes may disturb continuation of sorafenib therapy, eventually leading to a worse prognosis. Recently, a long duration of sorafenib treatment has been reported to be an important prognostic factor for overall survival . Of course, it is important to manage adverse events of sorafenib for a long duration of treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present muscle‐atrophy group, muscle wasting after starting sorafenib might have more frequently caused fatigue, asthenia, and physical disability compared to the non‐atrophy group, and resultant physical changes may disturb continuation of sorafenib therapy, eventually leading to a worse prognosis. Recently, a long duration of sorafenib treatment has been reported to be an important prognostic factor for overall survival . Of course, it is important to manage adverse events of sorafenib for a long duration of treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a long duration of sorafenib treatment has been reported to be an important prognostic factor for overall survival. 26,27 Of course, it is important to manage adverse events of sorafenib for a long duration of treatment. In our study, we found no significant differences in regard to the frequency of patients with adverse events, amount of sorafenib within the first 2 months after starting treatment, rate of discontinuing sorafenib, or TTP between the groups.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the association between treatment duration and survival, two previous studies have demonstrated that the duration of sorafenib treatment is an independent risk factor for survival. 33,34 These findings suggest that skeletal muscle mass seems to be associated with OS when there is no difference in the duration of sorafenib treatment. However, the duration of sorafenib treatment might be more important for OS than skeletal muscle mass if the duration of treatment differs between patients with LSMM and non-LSMM patients.…”
Section: Discussionmentioning
confidence: 82%
“…The study indicated that presarcopenia is a significant prognostic factor in patients with two or less negative prognostic factors (serum albumin level ≤ 3.5 g/dL, AFP level ≥ 100 ng/mL, the presence of bilateral lesions, or the presence of major portal vein invasion). Regarding the association between treatment duration and survival, two previous studies have demonstrated that the duration of sorafenib treatment is an independent risk factor for survival . These findings suggest that skeletal muscle mass seems to be associated with OS when there is no difference in the duration of sorafenib treatment.…”
Section: Discussionmentioning
confidence: 89%
“…In a Japanese study, 45.0% of 241 patients diagnosed with advanced hepatocellular carcinoma developed this syndrome. 2 , 3 …”
mentioning
confidence: 99%